Ontogeny of Myeloid Cells - De Kleer, Ismé; Willems, Fabienne; Lambrecht, Bart; Goriely, Stanislas (Frontiers in Immunology, 2014)
Granulocytes, monocytes, macrophages, and dendritic cells (DCs) represent a subgroup of leukocytes, collectively called myeloid cells. During the embryonic development of mammalians, myelopoiesis occurs in a stepwise fashion that begins in the yolk sac and ends up in the bone marrow. During this process, these early monocyte progenitors colonize various organs such as the brain, liver, skin and lungs and differentiate into resident macrophages that will self-maintain throughout life. DCs are constantly replenished from bone marrow precursors but can also arise from monocytes in inflammatory conditions. In this review, we summarize the different types of myeloid cells and discuss new insights into their early origin and development in mice and humans from fetal to adult life. We specifically focus on the function of monocytes, macrophages and DCs at these different developmental stages and on the intrinsic and environmental influences that may drive these adaptations.